Optimal BD-ZF precoder for multi-user MIMO downlink transmission - Yao, Rugui; Nan, Huani; Xu, Juan; Li, Geng (Electronics letters, 2015)
For multi-user MIMO downlink transmission, a block-diagonal zero-forcing (BD-ZF) precoder is usually used to suppress multi-user interference. In the case of a large number of transmitted antennas installed at the base station, there exists a larger nullspace than the precoder requires. An optimal BD-ZF precoder is developed to maximise throughput using the determinant maximisation technique. It helps to gather all gain for the transmission of each user. Numerical results validate that the precoder obtains throughput improvement.